130k views
5 votes
14. 2057 Q.No. 1(a) Sum to infinity:
1 + 3x + 5x2 + 7x3 +... (-1<x<1).​

1 Answer

2 votes

The sum appears to be


\displaystyle\sum_(n=0)^\infty(2n+1)x^n

I'll assume you want to find out what function this sum converges to.

Let


f(x)=\frac1{1-x}=\displaystyle\sum_(n=0)^\infty x^n

with -1 < x < 1. Differentiating gives


f'(x)=\frac1{(1-x)^2}=\displaystyle\sum_(n=0)^\infty nx^(n-1)=\sum_(n=1)^\infty nx^(n-1)=\sum_(n=0)^\infty(n+1)x^n

So we have


\displaystyle\sum_(n=0)^\infty(2n+1)x^n=f'(x)+xf'(x)


\displaystyle\sum_(n=0)^\infty(2n+1)x^n=(1+x)/((1-x)^2)

User D Whelan
by
5.4k points